Labor market dynamics and development - Kevin Donovan; Will Jianyu Lu; Todd Schoellman (Yale University, Economic Growth Center, 2020)
We build a dataset of harmonized rotating panel labor force surveys covering 42 countries across a wide range of development and document three new empirical findings on labor market dynamics. First, labor market flows (job-finding rates, employment-exit rates, and job-to-job transition rates) are two to three times higher in the poorest as compared with the richest countries. Second, employment hazards in poorer countries decline more sharply with tenure; much of their high turnover can be attributed to high separation rates among workers with low tenure. Third, wage-tenure profiles are much steeper in poorer countries, despite the fact that wage-experience profiles are flatter. We show that these facts are consistent with theories with endogenous separation, particularly job ladder and learning models. We disaggregate our results and investigate possible driving forces that may explain why separation operates differently in rich and poor countries.
Keywords: O1; J6; 330; job flows; job-finding rate; separation rate; selection